IMPLEMENTATION OF A PRACTICUM-BASED INQUIRY LEARNING MODEL TO IMPROVE STUDENT LEARNING OUTCOMES ON TEMPERATURE AND HEAT: CLASSROOM ACTION RESEARCH - Lestari, Ayu Resti; Aviyanti, Lina; Gani, Amalia Weka; Rahmayani, Erni; Ratri, Safitri Yosita (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to determine the enhancement of student learning outcomes by employing a practicum-based inquiry learning model focusing on temperature and heat. This classroom action research was conducted involving 36 students in grade XI at SMAN 2 Lembang 2022-2023 school year. The instruments consist of tests, questionnaires, and observations were utilized for data collection. Data analysis involved calculating the mean scores for affective, psychomotor, and cognitive domains, along with the percentage of students meeting or surpassing the KKM. Findings revealed improvements in learning outcomes across all domains throughout the pre-cycle, cycle 1, and cycle 2. Furthermore, the percentage of students achieving above the KKM in the cognitive domain, increased from the pre-cycle by 66%, in cycle 1 by 77%, and in cycle 2 by 92%. The teaching and learning implementation scores for cycles 1 and 2 were 3.0 and 3.3 respectively, both of which fall into the high category.